Management Of Teacher Pedagogic Competency Development In Improving Teacher Performance Productive Network Computer Engineering (Case Study Of SMKS Kosgoro and SMKS Nusantara Bogor City) - Karno Diharjo, Mantri; Muchtar, Hendi S.; Iriantara, Yosal; Rostini, Deti (International Journal of Educational Research & Social Sciences, 2022)
This research is motivated by the implementation of pedagogic competence development in general has not been able to improve its quality because it does not yet have a superior quality culture. This study aims to determine the implementation of the management of teacher pedagogical competence development in an effort to improve their performance. The theories in this research are: management theory, coaching (empowerment), competence, performance and six value systems. This study uses a descriptive exploratory method with a qualitative approach to the type of case study that focuses on one particular object as a case and makes general conclusions based on scientific facts. The results of the research in general have obtained an overview of the implementation of management of pedagogic competence development in an effort to improve its performance. Specifically, it is concluded that: (1) Planning for teacher competency development to improve teacher pedagogic competence has a 5-year program formulation and an annual coaching program. (2) The organization of teacher competency development to improve teacher pedagogic competence is prepared by the School Team, consisting of school principals, vice principals and heads of the Computer Network Engineering program. (3) Implementation of teacher competency development to improve teacher pedagogic competence is sometimes not in accordance with the programmed schedule/time and established procedures, as well as operational cost constraints. (4) Supervision of teacher competency development to improve teacher pedagogic competence has been carried out by the Head by recommending suggestions to teachers to make follow-up plans, (5) Factors that support teacher competency development to improve teacher pedagogic competence are good activity planning according to the program and objectives; high enthusiasm and passion for the profession. As for the obstacles in the implementation of the development of pedagogical competence include: a) Lack of competent teachers; b) productive teachers of Network Computer Engineering have not fully utilized the data obtained from the coaching; and c) productive teachers of Network Computer Engineering have not carried out their duties according to their duties and responsibilities. (6) Efforts made to overcome obstacles and obstacles in the implementation of teacher pedagogical competence development to improve the performance of productive teachers in Networking Computer Engineering are: a) maintaining communication always connected and monitoring more intensely, b) Principal recommending the results of coaching to the Foundation , c) sharing good practices of knowledge and experience with other productive teachers; and d) Utilizing information technology in the form of applications and social media to facilitate the implementation of coaching. The research product of the hypothetical model is depicted in a schematic diagram and its explanation.